Prevalence of an Entomopathogenic Fungus, Hirsutella citriformis on Leucaena Psyllid, Heterapsylla cubana, in Malaysia - Sajap, Ahmad Said (Universiti Putra Malaysia Press, 1993)
The leucaena psyllid, Heteropsylla cubana Crawford (Homoptera: Psyllidae) is a serious exotic pest of Leucaena leucocephala (Lam.) (Leguminosae) in Southeast Asia, Pacific Islands, Hawaii and Australia. Even though the insect is already widespread throughout Malaysia, no information on the entomopathogens associated with this pest has been recorded. This study reports, for the first time, the occurrence of an entomopathogenic fungus, Hirsutella citriformis Speare (Deuteromycotina: Hyphomycetes) on the leucaena psyllid, H. cubana in Malaysia. Results from monthly sampling of the psyllid over a period of one year established that the leucaena psyllid, H. cubana was susceptible to infection by the fungus, H. citriformis. Dead psyllids were found mummified and cemented by cream-coloured mycelia to the leaves and branches of the leucaena plant. The results also showed that adult psyllids were more prone to fungal infection than nymphs. The adult population had an average infection rate of about 20% while nymphs had an infection rate of less than 2%.